2021
DOI: 10.1038/s41597-021-00987-8
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomes, metatranscriptomes and microbiomes of naturally decomposing deadwood

Abstract: Deadwood represents significant carbon (C) stock in a temperate forests. Its decomposition and C mobilization is accomplished by decomposer microorganisms – fungi and bacteria – who also supply the foodweb of commensalist microbes. Due to the ecosystem-level importance of deadwood habitat as a C and nutrient stock with significant nitrogen fixation, the deadwood microbiome composition and function are critical to understanding the microbial processes related to its decomposition. We present a comprehensive sui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 55 publications
1
10
0
Order By: Relevance
“…To test the performance of the intron prediction workflow, we used a selection of publicly available metagenomes that represent a wide range of terrestrial, aquatic and host‐associated habitats (Table S4) (Corrêa et al, 2020; Tláskal, Brabcová, Větrovský, López‐Mondéjar, et al, 2021). Assembled contigs from each metagenomic study were analysed by our pipeline SVMmycointron.…”
Section: Methodsmentioning
confidence: 99%
“…To test the performance of the intron prediction workflow, we used a selection of publicly available metagenomes that represent a wide range of terrestrial, aquatic and host‐associated habitats (Table S4) (Corrêa et al, 2020; Tláskal, Brabcová, Větrovský, López‐Mondéjar, et al, 2021). Assembled contigs from each metagenomic study were analysed by our pipeline SVMmycointron.…”
Section: Methodsmentioning
confidence: 99%
“…A comprehensive screening of temperate forest soil and leaf litter internal transcribed spacer (ITS) barcode sequences deposited in the GlobalFungi database (Větrovský et al, 2020) and analyzed for this review revealed 3,783,412 total yeast sequences belonging to 859 yeast species hypotheses (SHs); yeasts here were categorized in the database as "yeast" or "facultative yeast" as in Põlme et al (2020), with some manual curation (Table S1); and only samples with more than 5,000 fungal sequences were considered. Fungal ITS-targeting primers perform well with all important fungal lineages containing yeasts and with individual yeasts in a mock community (Větrovský et al, 2016(Větrovský et al, , 2019, and no significant polymerase chain reaction (PCR) bias is observed when comparing the yeast share in metagenomic data (without PCR) and ITS amplicon data (Tláskal et al, 2021); nor does there seem to be important DNA extraction bias against selected yeast taxa (Větrovský et al, 2016). This screening showed that the median yeast abundance in soil was significantly higher than in litter (Wilcoxon Rank-Sum test, W = 722,187, p = 2.9 Â 10 À15 ).…”
Section: Yeast Distributions From Environmental Sequencingmentioning
confidence: 99%
“…Although deadwood degradation contributes to release of CO 2 into the atmosphere, its nal degradation products also enrich soils with nutrients and recalcitrant organic matter (OM), assisting nutrient cycling and carbon storage in forest ecosystems (Baldrian et al, 2023). Here, we used deadwood samples from a natural mixed temperate forest in Central Europe, which were previously analyzed through bacterial genomics, metagenomics and metatranscriptomics using second generation high-throughput sequencing (Tláskal et al, 2021a(Tláskal et al, , 2021b(Tláskal et al, , 2017. These studies identi ed fungi and bacteria as the main contributors to deadwood microbiomes.…”
Section: Introductionmentioning
confidence: 99%